Nutritional factors associated with chronic non-communicable diseases - the Bambuí Project: a population-based study - Aline Cristine Souza Lopes; Luana Caroline dos Santos; Maria Fernanda Lima-Costa; Waleska Teixeira Caiaffa
The increase of chronic non-communicable diseases has been significant. The objective of this study was to identify factors related to food intake, anthropometry and biochemical measurements associated with chronic non-communicable diseases. It involved a cross-sectional study among a representative sample of adults and elderly people in Bambuí, Minas Gerais State, Brazil. Anthropometric, biochemical and nutrient intake data were evaluated. The study included 409 individuals (55.3% of whom were women), with a mean age of 40.6±16.0 years. There was found to be a 14% rate of obesity associated with high/very high triglycerides and arterial hypertension. Arterial hypertension was present in 22.4% of subjects and correlated with age > 60 years, insufficient protein intake, obesity and high cholesterol. Diabetes was found in 3.7% and was associated with large waist circumference, excessive saturated fatty acids and arterial hypertension. The factors associated with chronic non-communicable diseases were obesity, high total cholesterol, triglycerides and excessive consumption of saturated fatty acids. The identification of the nutritional factors associated with chronic non-communicable diseases can support future interventions.